Triple burden or triple strength? Exploring work-study-family balance among parents - Putri, Ghaissani Elsa; Satrya, Aryana (Edelweiss Applied Science and Technology, 2025)
This qualitative study explores how working parents pursuing higher education perceive their ability to balance work, study, and family life. Using semi-structured interviews with 12 participants, the research applied manual coding through open, axial, and selective stages to identify key themes. Time management and task delegation emerged as primary strategies for managing triple-role demands. All female participants reported experiencing burnout, whereas only half of the male participants expressed similar concerns. Each participant adopted different coping mechanisms to deal with burnout, with emotion-focused strategies appearing as the most common approach. The study shows that mothers still bear most caregiving duties and face greater social pressure than fathers when juggling work, study, and family roles. Female participants were the only ones who experienced guilt over the intricacy of several responsibilities. Furthermore, the study emphasizes the importance of support systems—family, employers, and universities—in assisting individuals in achieving balance. It also suggests that individuals’ perceptions of success in achieving work-study-family balance are not solely determined by their level of self-efficacy. No significant gender-based differences were found in the perceived attainment of balance across work, study, and family domains. Employers and universities must establish supportive policies to facilitate effective role balance among working student-parents.